Interfacial ketene via the photo‐Wolff rearrangement for the modification of monolayer protected gold nanoparticles. (29th May 2013) - Snell, Kristen E.; Johnson, Michel; Hesari, Mahdi; Ismaili, Hossein; Workentin, Mark S.
<x xml:space="preserve">Abstract</x> An interfacial diazoketone‐modified gold nanoparticle (AuNP) was prepared and characterized by 1H NMR and IR spectroscopy, TGA and TEM. Irradiation of the diazoketone leads to loss of nitrogen and the formation an interfacial ketene–AuNP via the photo‐Wolff rearrangement, evidenced by the loss of the characteristic C = N = N signal at 2068 cm−1 in the IR spectrum and the growth of a new signal at 2100 cm−1 indicative of the ketene. This ketene is relatively stable in the absence of added nucleophiles, but reacts quickly with oxygen nucleophiles illustrating the potential use of this ketene–AuNP as a template for a wide range of surface modifications. Copyright © 2013 John Wiley & Sons, Ltd.